Rhetorical strategies on www.iReport.com - Tereszkiewicz, Anna (Studia Linguistica Universitatis Iagellonicae Cracoviensis, 2011)
The study concentrates on the phenomenon of user-generated content on the internet. The article presents an introductory analysis of various rhetorical strategies used by the authors of commentaries on one of the popular user-contributory sites, i.e. www.iReport.com. The analysis of this site shows that there exists a range of diverse means of expression used by the enthusiasts of broadcasting online, involving the submission of written articles, live video commentaries, audio files and cartoons. The study shows that users shape the features of the content in different manners and resort to the use of a variety of rhetorical devices. To the main properties of discourse belong personalization, interactivity, use of figurative and vivid language.